2020
DOI: 10.7793/jcad.26.19-00015
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Detection of Inadequate Saphenous Vein by Noncontrast Three-dimensional Computed Tomography

Abstract: ─ 24 ─ I. Introduction Despite the widespread use and superior patency of the arterial graft for coronary artery bypass grafting (CABG), the saphenous vein (SV) continues to be the most commonly used graft. The SVs, however, sometimes have anatomical problems such as varicose veins, small or large diameter, and duplication. Ultrasonography has been the main modality for preoperative SV evaluation because of its simplicity and low invasiveness 1) ; however, it has drawbacks, such as a lack of objectiveness, poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Previously, we investigated the results of non-contrast 3D-CT SV evaluation in preoperative patients with CABG [2]. The results of our study, which included 54 patients, revealed that nearly 40% of the patients had SVs that were inappropriate for grafting.…”
mentioning
confidence: 95%
“…Previously, we investigated the results of non-contrast 3D-CT SV evaluation in preoperative patients with CABG [2]. The results of our study, which included 54 patients, revealed that nearly 40% of the patients had SVs that were inappropriate for grafting.…”
mentioning
confidence: 95%